PERFORMANCE OF ‘NANICÃO JANGADA’ BANANA PLANTS INTERCROPPED WITH WINTER COVER CROPS - AGUIAR,RICARDO SFEIR DE (2016)
ABSTRACT The use of cover crops species may be an important strategy in the pursuit of sustainability of agroecosystems, considering benefits to soil, such as improvements of physical and chemical characteristics, and weed control. The objective of this study was to evaluate the effect of winter cover crops and other soil managements on chemical soil properties, on the cycle, on the production of the first cycle and on the fruit quality of banana cv. Nanicão Jangada in Andirá – PR, Brazil. The experiment was carried out in a commercial. Planting of banana suckers from the grower area occurred in the first half of March 2011, with a spacing of 2.40 m between rows and 1.90 m between plants. The experiment was designed in randomized blocks with four replications and six plants per plot. The six treatments were: black oat (Avenastrigosa Schreb), forage turnip (Raphanus sativus L. var. oleiferus), consortium of black oat and forage turnip, chicken litter, residues of banana plants, and bare ground. The evaluations were vegetative development and life cycle of banana plants, yield and quality of fruits, soil chemical characterstics, and fresh and dry mass of green manures. The results were submitted to ANOVA (F Test), and Tukey test at 5 % probability. Black oat and black oat with forage turnip consortium were superior in biomass production. Systems of soil management had no effect on the variables, except in the periods between planting and flowering and between planting and harvest, which were shorter in the treatment of soil management with crop residues, longer in the treatment with forage turnip, and intermediate in the other treatments.